Spatio-temporal changes of riparian vegetation in the Monterrey hydrological subbasin, Nuevo León - Hernández-Cavazos, María Cecilia (2025)
The objective of this study was to determine the changes in the coverage of riparian vegetation in the Monterrey hydrological subbasin, considering four time periods: 1995-2008, 2008-2014, 2014-2022 and 1995-2022, to know the dynamic temporal space to lay the foundations for protection and conservation strategies by decision makers. Orthophotos and high-resolution satellite images Airbus Defense and Space, GeoEye-1 and Birdseye, as well as the supervised classification method and field validation were used to generate the land use and vegetation change maps. The net change, the annual rate of area loss and the relative change rate were determined. In 27 years (1995-2022) 805.06 hectares of riparian vegetation were lost. The period 2008-2014 presented the greatest loss of surface area (-67.22 ha/year), contrary to the period 2014-2022, which only experienced a loss of -1.53 ​​ha/year. The relative change rate of riparian vegetation for the entire study period (1995-2022) was -0.29%, while for soil without vegetation it was 0.45%. In the period 2008-2014, the highest rate of change occurred (-0.66%), while in the period 2014-2022 it was only -0.02%. The results of this study can serve as a basis for the establishment of conservation actions that allow maintaining this trend in the condition of the riparian vegetation cover; as well as contribute to future studies of this plant community in Mexico.